PENGARUH PENERAPAN LEMBAR KERJA SISWA BERBASIS SAINS TEKNOLOGI MASYARAKAT TERHADAP HASIL BELAJAR FISIKA KELAS VIII SMPN 18 PADANG - Nike Gusmedi (Universitas Negeri Padang, 2013)
This research based low learning outcome of the student in physic subject at school. The factors of low learning outcome are less involvement of the students in learning process, so that activities and creativity of student is low. The solution alternative of this problem is involve the student through application of worksheet based on Society Technology Science in physics learning. The population of research is SMPN 18 Padang. The sample take by using Purposif Sampling technique. The research outcome show that there is significant impact of treatment physics outcome at class VIII SMPN 18 Padang in quantitative on the real level 0,05 Keywords : Worksheet, STS, Physics, Learning Outcomes